DISPARITAS PEMIDANAAN SEBAGAI DASAR ALASAN PENGAJUAN UPAYA HUKUM PENINJAUAN KEMBALI: Criminal Disparity as the Basis for Filing a Review Legal Remedy - Sandrina Aisha Devi; Setiyono (Reformasi Hukum Trisakti, 2026)
The Indonesian criminal justice system aims to ensure justice and protection for convicts, one of which is through the legal remedy of Judicial Review (PK) as stipulated in the Criminal Procedure Code (KUHAP). The Criminal Procedure Code limits the grounds for Judicial Review to 3 (three) categories: the existence of new circumstances (novum), conflicting decisions, and judicial error/manifest error. However, it turns out that there is one Supreme Court Decision Number 270 PK/Pid.Sus/2020 based on the reason of disparity. The question is whether the legal difference in Supreme Court Decision Number 270 PK/Pid.Sus/2020 constitutes a judicial error/manifest error according to Article 263 of the Criminal Code. The researcher integrated normative legal research with qualitative descriptive analysis. The discussion and findings indicate that differences in sentencing are not grounds for Judicial Review, but can be a judicial error/manifest error if there is a legal error in the evaluation. This analysis concludes that inequity in sentencing can be used for Judicial Review if it causes manifest injustice.